Impact of oil prices on CO2 emissions in Iraq: empirical methodology using ARDL versus NARDL methods - Hasanain Ali Hussein; Kamel Helali (Peerian Journals Publishing, 2023)
The objective of this work is to evaluate the impact of increasing the taxation of petroleum products on economic activity in Iraq, CO2 emissions and household welfare. To this end, two methods, linear (ARDL) and non-linear (NARDL), were applied to the Iraqi economy, based on the period from 1970 to 2021. The results show that, among the various scenarios simulated, CO2 emissions have a greater ecological impact on petroleum products. The price of oil ensures both a reduction in CO2 emissions and an improvement in household welfare. This is due to the composition of macroeconomic variables, corresponding to an increase in the subsidy of this product.
Keywords: Oil prices; CO2 emissions; ARDL